### Hess' Law of Constant Heat SummationUsing three equations and their enthalpies

Germain Henri Hess, in 1840, discovered a very useful principle which is named for him:

The enthalpy of a given chemical reaction is constant, regardless of the reaction happening in one step or many steps.

Another way to state Hess' Law is:

If a chemical equation can be written as the sum of several other chemical equations, the enthalpy change of the first chemical equation equals the sum of the enthalpy changes of the other chemical equations.

Example #1: Calculate the enthalpy for this reaction:

 2C(s) + H2(g) ---> C2H2(g) ΔH° = ??? kJ

Given the following thermochemical equations:

 C2H2(g) + 5⁄2O2(g) ---> 2CO2(g) + H2O(ℓ) ΔH° = -1299.5 kJ C(s) + O2(g) ---> CO2(g) ΔH° = -393.5 kJ H2(g) + 1⁄2O2(g) ---> H2O(ℓ) ΔH° = -285.8 kJ

Solution:

1) Determine what we must do to the three given equations to get our target equation:

a) first eq: flip it so as to put C2H2 on the product side
b) second eq: multiply it by two to get 2C
c) third eq: do nothing. We need one H2 on the reactant side and that's what we have.

2) Rewrite all three equations with changes applied:

 2CO2(g) + H2O(ℓ) ---> C2H2(g) + 5⁄2O2(g) ΔH° = +1299.5 kJ 2C(s) + 2O2(g) ---> 2CO2(g) ΔH° = -787 kJ H2(g) + 1⁄2O2(g) ---> H2O(ℓ) ΔH° = -285.8 kJ

Notice that the ΔH values changed as well.

3) Examine what cancels:

2CO2 ⇒ first & second equation
H2O ⇒ first & third equation
52O2 ⇒ first & sum of second and third equation

4) Add up ΔH values for our answer:

+1299.5 kJ + (-787 kJ) + (-285.8 kJ) = +226.7 kJ

Example #2: Calculate the enthalpy of the following chemical reaction:

CS2(ℓ) + 3O2(g) ---> CO2(g) + 2SO2(g)

Given:

 C(s) + O2(g) ---> CO2(g) ΔH = -393.5 kJ/mol S(s) + O2(g) ---> SO2(g) ΔH = -296.8 kJ/mol C(s) + 2S(s) ---> CS2(ℓ) ΔH = +87.9 kJ/mol

Solution:

1) What to do to the data equations:

leave eq 1 untouched (want CO2 as a product)
multiply second eq by 2 (want to cancel 2S, also want 2SO2 on product side)
flip 3rd equation (want CS2 as a reactant)

2) The result:

 C(s) + O2(g) ---> CO2(g) ΔH = -393.5 kJ/mol 2S(s) + 2O2(g) ---> 2SO2(g) ΔH = -593.6 kJ/mol <--- note multiply by 2 on the ΔH CS2(ℓ) ---> C(s) + 2S(s) ΔH = -87.9 kJ/mol <--- note sign change on the ΔH

3) Add the three revised equations. C and 2S will cancel.

4) Add the three enthalpies for the final answer.

Example #3: Given the following data:

 SrO(s) + CO2(g) ---> SrCO3(s) ΔH = -234 kJ 2SrO(s) ---> 2Sr(s) + O2(g) ΔH = +1184 kJ 2SrCO3(s) ---> 2Sr(s) + 2C(s, gr) + 3O2(g) ΔH = +2440 kJ

Find the ΔH of the following reaction:

C(s, gr) + O2(g) ---> CO2(g)

Solution:

1) Analyze what must happen to each equation:

a) first eq ⇒ flip it (this put the CO2 on the right-hand side, where we want it)

b) second eq ⇒ do not flip it, divide through by two (no flip because we need to cancel the SrO, divide by two because we only need to cancel one SrO)

c) third equation ⇒ flip it (to put the SrCO3 on the other side so we can cancel it), divide by two (since we need to cancel only one SrCO3)

Notice that what we did to the third equation also sets up the Sr to be cancelled. Why not also multiply first equation by two (to get 2SrO for canceling)? Because we only want one CO2 in the final answer, not two. Notice also that I ignored the oxygen. If everything is right, the oxygen will take care of itself.

2) Apply all the above changes (notice what happens to the ΔH values):

 SrCO3(s) ---> SrO(s) + CO2(g) ΔH = +234 kJ SrO(s) ---> Sr(s) + 1⁄2O2(g) ΔH = +592 kJ Sr(s) + C(s, gr) + 3⁄2O2(g) ---> SrCO3(s) ΔH = -1220 kJ

3) Here is a list of what gets eliminated when everything is added:

SrCO3, SrO, Sr, 12O2

The last one comes from 32O2 on the left in the third equation and 12O2 on the right in the second equation.

4) Add the equations and the ΔH values:

+234 + (+592) + (-1220) = -394

 C(s, gr) + O2(g) ---> CO2(g) ΔH°f = -394 kJ

Notice the subscripted f. This is the formation reaction for CO2 and its value can be looked up, either in your textbook or online.

Example #4: Given the following information:

 2NO(g) + O2(g) ---> 2NO2(g) ΔH = -116 kJ 2N2(g) + 5O2(g) + 2H2O(ℓ) ---> 4HNO3(aq) ΔH = -256 kJ N2(g) + O2(g) ---> 2NO(g) ΔH = +183 kJ

Calculate the enthalpy change for the reaction below:

 3NO2(g) + H2O(ℓ) ---> 2HNO3(aq) + NO(g) ΔH = ???

Solution:

1) Analyze what must happen to each equation:

a) first eq ⇒ flip; multiply by 32 (this gives 3NO2 as well as the 3NO which will be necessary to get one NO in the final answer)

b) second eq ⇒ divide by 2 (gives two nitric acid in the final answer)

c) third eq ⇒ flip (cancels 2NO as well as nitrogen)

2) Comment on the oxygens:

a) step 1a above puts 32O2 on the right
b) step 1b puts 52O2 on the left
c) step 1c puts 22O2 on the right

In addition, a and c give 52O2 on the right to cancel out the 52O2 on the left.

3) Apply all the changes listed above:

 3NO2(g) ---> 3NO(g) + 3⁄2O2(g) ΔH = +174 kJ N2(g) + 5⁄2O2(g) + H2O(ℓ) ---> 2HNO3(aq) ΔH = -128 kJ 2NO(g) ---> N2(g) + O2(g) ΔH = -183 kJ

4) Add the equations and the ΔH values:

+174 + (-128) + (-183) = -137 kJ

 3NO2(g) + H2O(ℓ) ---> 2HNO3(aq) + NO(g) ΔH = -137 kJ

Example #5: Calculate ΔH for this reaction: CH4(g) + NH3(g) ---> HCN(g) + 3H2(g)

given:

 N2(g) + 3 H2(g) ---> 2 NH3(g) ΔH = -91.8 kJ C(s) + 2 H2(g) ---> CH4(g) ΔH = -74.9 kJ H2(g) + 2 C(s) + N2(g) ---> 2 HCN(g) ΔH = +270.3 kJ

Solution:

1) Analyze what must happen to each equation:

a) first eq ⇒ flip and divide by 2 (puts one NH3 on the reactant side)
b) second eq ⇒ flip (puts one CH4 on the reactant side)
c) third eq ⇒ divide by 2 (puts one HCN on the product side)

2) Rewite all equations with the changes:

 NH3(g) ---> 1⁄2N2(g) + 3⁄2H2(g) ΔH = +45.9 kJ <--- note sign change & divide by 2 CH4(g) ---> C(s) + 2 H2(g) ΔH = +74.9 kJ <--- note sign change 1⁄2H2(g) + C(s) + 1⁄2N2(g) ---> HCN(g) ΔH = +135.15 kJ <--- note divided by 2

3) What cancels when you add the equations:

12N2(g) ⇒ first and third equations
C(s) ⇒ second and third equations
12H2(g) on the left side of the third equation cancels out 12H2(g) on the right, leaving a total of 3H2(g) on the right (which is what we want)

4) Calculate the ΔH for our reaction:

+45.9 kJ plus +74.9 kJ plus +135.15 = 255.95 kJ = 260. kJ (note three sig figs)

Example #6: Determine the heat of reaction for the oxidation of iron:

2Fe(s) + 32O2(g) ---> Fe2O3(s)

given the thermochemical equations:

 2Fe(s) + 6H2O(ℓ) ---> 2Fe(OH)3(s) + 3H2(g) ΔH = +322 kJ Fe2O3(s) + 3H2O(ℓ) ---> 2Fe(OH)3(s) ΔH = +289 kJ 2H2(g) + O2(g) ---> 2H2O(ℓ) ΔH = –572 kJ

Solution:

1) Here's what needs to be done:

 2Fe(s) + 6H2O(ℓ) ---> 2Fe(OH)3(s) + 3H2(g) ΔH = +322 kJ <--- nothing was done 2Fe(OH)3(s) ---> Fe2O3(s) + 3H2O(ℓ) ΔH = -289 kJ <--- reversed equation 3H2(g) + 3⁄2O2(g) ---> 3H2O(ℓ) ΔH = –858 kJ <--- multiplied through by 3⁄2

2) Adding up the equations gives the target equation. Adding the enthalpies gives us our answer:

2Fe(s) + 32O2(g) ---> Fe2O3(s) ΔH = -825 kJ

Note how the multiplying factor doesn't have to be an integer value.

Example #7: Using the following thermochemical equations, calculate the standard enthalpy of combustion for one mole of liquid acetone (C3H6O).

 3C(s) + 3H2(g) + 1⁄2O2(g) ---> C3H6O(ℓ) ΔH° = -285.0 kJ C(s) + O2(g) ---> CO2(g) ΔH° = -394.0 kJ H2(g) + 1⁄2O2(g) ---> H2O(ℓ) ΔH° = -286.0 kJ

Solution:

1) The combustion of liquid acetone is the target equation. Write (and balance) it:

C3H6O(ℓ) + 4O2(g) ---> 3CO2(g) + 3H2O(ℓ)

2) The first data equation needs to be reversed, so as to put acetone on the reactant side. Here are all three data equations with the first one changed:

 C3H6O(ℓ) ---> 3C(s) + 3H2(g) + 1⁄2O2(g) ΔH° = +285.0 kJ C(s) + O2(g) ---> CO2(g) ΔH° = -394.0 kJ H2(g) + 1⁄2O2(g) ---> H2O(ℓ) ΔH° = -286.0 kJ

Note the sign change in the enthalpy when the equation is reversed.

3) The second data equation needs to be changed to create a situation where the 3C(s) will cancel when the equations are added together:

 C3H6O(ℓ) ---> 3C(s) + 3H2(g) + 1⁄2O2(g) ΔH° = +285.0 kJ 3C(s) + 3O2(g) ---> 3CO2(g) ΔH° = -1182.0 kJ H2(g) + 1⁄2O2(g) ---> H2O(ℓ) ΔH° = -286.0 kJ

Note that the enthalpy was also multiplied by three.

4) The 3H2(g) (present in the first data equation) also needs to be removed from the final answer. Another multiplication by 3 is used:

 C3H6O(ℓ) ---> 3C(s) + 3H2(g) + 1⁄2O2(g) ΔH° = +285.0 kJ 3C(s) + 3O2(g) ---> 3CO2(g) ΔH° = -1182.0 kJ 3H2(g) + 3⁄2O2(g) ---> 3H2O(ℓ) ΔH° = -858.0 kJ

Note that the enthalpy was also multiplied by three.

5) Add the three data equations together to recover the target equation laid out in step 1. Note the following:

12O2(g) will cancel from each side, leaving 4O2(g) on the left-hand side.

The enthalpies are added together to obtain the final answer of -1755 kJ.